Determinants of selenoneine concentration in red blood cells of Inuit from Nunavik (Northern Québec, Canada) - Lemire, Mélanie; Little, Matthew; Achouba, Adel; Ayotte, Pierre; Dumas, Marie-Pierre; Ouellet, Nathalie (Environment International, 2020)
Selenium (Se) is a trace mineral essential to human health, and is especially abundant in marine foods consumed by Inuit populations in Nunavik (northern Quebec, Canada), leading to exceptionally high whole blood Se levels. While most epidemiological studies to date examine plasma or whole blood Se, little is known about the health implications of specific Se biomarkers (e.g. selenoproteins and small Se compounds). Selenoneine, a novel Se compound, is found in high concentrations in marine foods (and particularly beluga mattaaq) and the red blood cells (RBCs) of populations that consume them. We report here RBC selenoneine concentrations in a population of Inuit adults (n = 885) who participated in the Qanuippitaa? 2004 survey. Simple associations between RBC selenoneine and other Se and mercury (Hg) biomarkers were assessed using Spearman correlations and linear regressions. Wilcoxon ranksum tests were used to examine differences in biomarkers and characteristics between tertiles of RBC selenoneine concentration. A multiple linear regression analysis was used to determine factors (sociodemographic, lifestyle, and dietary) associated with RBC selenoneine concentrations. Selenoneine comprised a large proportion of whole blood Se and RBC Se in this population. Age and sex-adjusted geometric mean RBC selenoneine concentration was 118 μg/L (range: 1-3226 μg/L) and was much higher (p = 0.001) among women (150.3 μg/L) than men (87.6 μg/L) across all regions of Nunavik after controlling for age, region, and diet. RBC selenoneine was highly correlated with RBC Se (rs = 0.96, p < 0.001) and whole blood Se (rs = 0.89, p < 0.001), but only weakly correlated with plasma Se (rs = 0.13, p < 0.001). Overall, increasing age (standardized β = 0.24), higher body-mass index (BMI; β = 0.08), female sex (β = 0.10), living in a Hudson Strait community (compared to Hudson Bay and Ungava Bay; β = 0.38), and consuming beluga mattaaq (g/day; β = 0.19) were positively associated with RBC selenoneine. Meanwhile, consumption of ...